Dosing of Extracorporeal Cytokine Removal In Septic Shock (DECRISS): protocol of a prospective, randomised, adaptive, multicentre clinical trial - Péter Hegyi; Bálint Erőss; Noémi Zádori; Noémi Gede; Zsolt Márton; Anna Kanjo; Zsolt Molnar; Lajos Szakó; Tamás Kiss; Manu L N G Malbrain; Konstanty Szuldrzynski; Jakub Szrama; et al. (BMJ Open)
Introduction Sepsis and septic shock have mortality rates between 20% and 50%. In sepsis, the immune response becomes dysregulated, which leads to an imbalance between proinflammatory and anti-inflammatory mediators. When standard therapeutic measures fail to improve patients’ condition, additional therapeutic alternatives are applied to reduce morbidity and mortality. One of the most recent alternatives is extracorporeal cytokine adsorption with a device called CytoSorb. This study aims to compare the efficacy of standard medical therapy and continuous extracorporeal cytokine removal with CytoSorb therapy in patients with early refractory septic shock. Furthermore, we compare the dosing of CytoSorb adsorber device changed every 12 or 24 hours.Methods and analysis It is a prospective, randomised, controlled, open-label, international, multicentre, phase III study. Patients fulfilling the inclusion criteria will be randomly assigned to receive standard medical therapy (group A) or—in addition to standard treatment—CytoSorb therapy. CytoSorb treatment will be continuous and last for at least 24 hours, CytoSorb adsorber device will be changed every 12 (group B) or 24 hours (group C). Our primary outcome is shock reversal (no further need or a reduced (≤10% of the maximum dose) vasopressor requirement for 3 hours) and time to shock reversal (number of hours elapsed from the start of the treatment to shock reversal).Based on sample size calculation, 135 patients (1:1:1) will need to be enrolled in the study. A predefined interim analysis will be performed after reaching 50% of the planned sample size, therefore, the corrected level of significance (p value) will be 0.0294.Ethics and dissemination Ethics approval was obtained from the Scientific and Research Ethics Committee of the Hungarian Medical Research Council (OGYÉI/65049/2020). Results will be submitted for publication in a peer-reviewed journal.Trial registration number NCT04742764; Pre-results.